Informal learning in continued professional development context: a missing link / Fadilah Puteh, Maniam Kaliannan and Nafis Alam - Puteh, Fadilah; Kaliannan, Maniam; Alam, Nafis (Faculty of Administrative Science and Policy Studies, 2015)
Talent management is a critical component of Human Resource Management (HRM) especially in the increasing world of globalization. Organizations are investing huge amount of money in attracting, developing and retaining the right human capital. In this context, Human Resource Development (HRD) as one of HRM component that focuses on 'nurturing' employee's knowledge, skills and abilities (KSA) plays a vital role in achieving the above objective. HRD does not only focus on development of skills but also focuses on the personal development of employees and organisation development at a broader range. HRD as a discipline has moved to embrace the concept of Continued Professional Development (CPD) that promote continuous or lifelong learning to develop and to ensure the up-to-date KSA among organisational members. CPD calls upon organisation to encourage, support, and provide favourable environment for employees to engage in continuous learning as to combat 'professional obsolete syndrome' or diminution of employee competency. This is important for the employees to remain relevant and current as well as for organisation to remain competitive. Literatures on CPD suggested that learning can take place in three dimensions i.e. formal, non-formal and informal learning. However, discussion on the third learning component which is informal learning is still vague and under-researched and always forgotten. While formal and non-formal learning focus are mainly on institutional structure and considered as traditional approaches to CPD and can be outsourced when appropriate; informal learning on the other hand, is centred on learner and has no boundary. Studies show that informal learning has a great potential to fills in knowledge and skills gap that are not covered by formal and non-formal learning. Though research has shown that informal learning is generally effective, little is known about the informal learning in CPD or lifelong learning context. There is an urgent need to ensure that informal learning component is embedded in the context of structured CPD or lifelong learning. Given the above context, the aim of this paper is to explore and identify key CPD components in the literature review especially informal learning. In addition it explores the missing link between informal learning and CPD.